Platelet Activation Is Limited during Transcatheter Aortic Valve Implantation in Patients on Aspirin Monotherapy and without per Procedural Clinical Complications - Dumonteil, Nicolas; Levade, Marie; Garcia, Cédric; Lhermusier, Thibault; Series, Jennifer; Le Faouder, Pauline; Marcheix, Bertrand; Payrastre, Bernard; Carrié, Didier; Sié, Pierre (TH Open, 2019)
Transcatheter aortic valve implantation (TAVI) is an established treatment option for symptomatic patients with severe aortic valve stenosis (AS). During and early after the procedure, both ischemic events (predominantly stroke) and bleedings remain prevalent. The optimal antithrombotic regimen is still debated. Single- versus dual-antiplatelet therapy is associated with a lower rate of severe bleeding, without difference in thrombotic complications. Although platelets have been empirically targeted, little is known on their contribution to these events primarily related to embolization of thrombotic material and tissue-derived debris from the wounded aortic valve and large vessels. The objective of this study was to assess local platelet activation in blood sampled in the ascending aorta immediately before and within minutes postimplantation. A series of 18 patients with AS on monotherapy with aspirin successfully underwent TAVI with the self-expandable Medtronic CoreValve by transfemoral route. No clinical thrombotic complication occurred at 30-day follow-up. Compared with patients with stable coronary artery disease unscathed of AS and similarly treated by low-dose aspirin, AS patients displayed a chronic state of platelet activation before TAVI, assessed in venous blood using various biomarkers. However, per procedure, in aortic blood, no change occurred between the two time points in the plasma levels of serotonin or 12-lipoxgenase products, or membrane exposure of granule markers CD62-P and CD63. Our results suggest that local acute platelet activation is limited during TAVI on monotherapy with aspirin.
Keywords: platelet activation; aortic valve stenosis; transcatheter aortic valve implantation